Serosurvey for antibodies against Brucella abortus and Leptospira interrogans in pampas deer from Brazil - Mathias, L. A.; Girio, RJS; Duarte, JMB (Wildlife Disease Assn, Inc, 1999)
A survey for antibodies against Brucella abortus, and Leptospira interrogans was conducted on 17 pampas deer (Ozotocerus bezoarticus) from Pantanal Matogrossense (State of Mato Grosso do Sul, Brazil) and on 24 pampas deer from Parque Nacional de Emas (State of Goias, Brazil). Antibodies against B. abortus were detected by plate ag glutination, rose Bengal, and complement fixation tests, antibodies against Leptospira interrogans were detected by the microscopic agglutination test. All sera were negative for B. abortus antibodies and all deer sera from Parque Nacional de Emas were negative for L. interrogans antibodies. Four (24%) of 17 sera from Pantanal Matogrossense were positive for L. interrogans serovar (n = 2) hardjo, wolffi (n = 1) and mini (n = 1). While these diseases do not appear to be of major importance to the health status of Pampas deer, it appears that deer are reservoir for leptospirosis in one of the study areas.
Keywords: Brucella abortus; brucellosis; Leptospira interrogans; Leptospirosis; Ozotoceros bezoarticus; Pampas deer; serologic survey